Genotyping and phylogenetic analysis of human Papillomaviruses from women with genital warts - Ghufran M. Al Azzawi; Anmar A. AlTaie (Romanian Journal of Infectious Diseases)
Background and objectives. The pathophysiology of Human Papillomavirus (HPV) infections is dependent on the genotype of virus, the host immune system and the local environmental conditions. HPV infections are linked to a variety of benign and malignant disorders. Anogenital warts is a Sexually Transmitted Infection (STI) primarily caused by Low-Risk HPV (LR-HPV) genotypes 6 and 11. The aims were to Investigation of the prevalence and genotypic distribution of HPV in women with genital warts in Mosul/Iraq, HPV-DNA sequencing and Phylogenetic analysis including minimum spanning trees of amplified HPV L1 gene comparison the present sequences with similar genotypes in GenBank – National Center Biotechnology Information (NCBI) using mega-7-software. Materials and methods. A total of 150 samples were collected from women with genital wart infections. Polymerase Chain Reaction (PCR) was performed using GP+5/GP+6 and MY09/MY11 consensus primers. Results. About 84.6% prevalence of HPV genotypes. The highest frequency (32% and 28.6%) were observed in the 19-28 and 29-38 age groups. Conclusion. Women in Mosul, Iraq, who have genital warts are more likely to have different genotypes of HPV. HPV 11 type was found to be the most common, followed HPV6 and HPV10 as LR HPV, while HPV 16 and HPV45 were the most common as HR HPV. The analysis of the phylogenetic tree revealed a genetic relationship between our isolates and global isolates ranging from (10-100%) bootstrap ratio this indicating phylogenetic relationships (divergent and convergent evolution) this was meant the diversity in origin of the various genotypes common in Mosul, Iraq.